Data recovery aware garbage collection mechanism in flash-based storage devices - Paik, Joon Young; Jin, Rize; Chung, Tae Sun (IEICE Transactions on Information and Systems, 2018)
In terms of system reliability, data recovery is a crucial capability. The lack of data recovery leads to the permanent loss of valuable data. This paper aims at improving data recovery in flash-based storage devices where extremely poor data recovery is shown. For this, we focus on garbage collection that determines the life span of data which have high possibility of data recovery requests by users. A new garbage collection mechanism with awareness of data recovery is proposed. First, deleted or overwritten data are categorized into shallow invalid data and deep invalid data based on the possibility of data recovery requests. Second, the proposed mechanism selects victim area for reclamation of free space, considering the shallow invalid data that have the high possibility of data recovery requests. Our proposal prohibits more shallow invalid data from being eliminated during garbage collections. The experimental results show that our garbage collection mechanism can improve data recovery with minor performance degradation.
Keywords: Data recovery; Flash translation layer; Free spaces; Garbage collection; NAND flash memory; Performance degradation; Storage systems; System reliability; Data recovery; Flash Translation Layer (FTL); NAND flash memory; Storage system